Nationwide rates of limited fasciectomy for Dupuytren’s contracture: data from the Finnish National Registry - Mikko Räisänen; Teemu Valtteri Karjalainen; Tuomas Tapani Huttunen; Ville Matti Mattila; Aleksi Rafael Reito; Olli Ville Leppänen; Janne Johannes Soikkeli; Jarkko Juhani Jokihaara (Journal of Plastic Surgery and Hand Surgery)
Dupuytren’s contracture (DC) is often treated with limited fasciectomy (LF), while percutaneous treatment options are gaining popularity. The recent trends in the incidence rates of LF are not well known. Our study aimed to investigate the incidence rates of LF over time, and we collected nationwide data on all LF performed between January 1, 1997 and December 31, 2018.